TOEFL iBT prep plus 2018-2019 : (Kaplan Publishing, 2017)
Provides strategies, tips, and four practice tests covering listening, reading, writing, and speaking skills and is thematically arranged by history, science, education, business, social science, arts, technology, and entertainment.